On The Switching Control Of The DC–DC Zeta Converter Operating In Continuous Conduction Mode - Sarkawi, Hafez; Ohta, Yoshito; Rapisarda, Paolo (John Wiley and Sons Inc, 2021)
Here, a switching control mechanism for the stabilization of a DC–DC zeta converter operating in continuous conduction mode is proposed. The switching control algorithm is based on a control Lyapunov function and extends the method proposed for a two-dimensional boost converter model presented in the literature to a four-dimensional zeta converter model. The local asymptotical stability of the operating point is established using LaSalle’s invariance principle for differential inclusions. By applying spatial regularization, a modified switching control algorithm reduces the switching frequency and keeps the state-trajectory around a neighbourhood of the operating point. The method works well even if the operation point changes significantly and it is valid for both step-up and step-down operations. Furthermore, by approximating the state-trajectory near the operating point,an explicit relation between the modified switching algorithm and the switching frequency is obtained, which allows to choose systematically the desired switching frequency for the converter to operate. The effectiveness of the proposed method is illustrated with simulation results.